Successful Treatment of Unexplained Secondary Infertility by Ayurveda- A Case Study - Bhavsar Megha Nandkishor; Mehere Seema Chandrakant (AYUSHDHARA, 2021)
Secondary infertility indicates previous pregnancy but failure to conceive subsequently. Incidences of secondary infertility are increasing day by day. Many factors like age, hectic schedule, stress, diet, unhealthy lifestyle are responsible for it. Psychological stress disturbs overall health of women by inducing generation of reactive oxygen species and thereby oxidative stress. This oxidative stress may hamper the health of ovaries, oocyte quality and causes female reproductive health disorders. Aim: To study the effect of Ayurvedic treatment in management of unexplained secondary infertility. Objective: To access the effect of Ayurvedic management of unexplained secondary infertility. Methodology: It is a single case study of unexplained secondary infertility. Case description: A 38 years old female Hindu patient came in YMT OPD of Streeroga and Prasutitantra anxious for child since 3 years. She had a history of 2 MTPs, one before and one after her 5 year old female child. Her last MTP was done in 2015. After that she was actively trying to conceive around last 3 years but couldn’t conceive again in spite of regular unprotected coitus. She was advised to do ovulation study and HSG but she was not willing to do investigations, but as per history, her schedule was very hectic and stressful treatment: She was advised Ayurvedic oral medications along with Panchkarma. Outcome: After four months of treatment she conceived. Conclusion: Ayurvedic management can act as an anti-stress and antioxidant agent thereby improving the reproductive health of women and increasing their chances of conception.